2021
DOI: 10.1038/s41587-021-01019-x
|View full text |Cite
|
Sign up to set email alerts
|

Wireless closed-loop optogenetics across the entire dorsoventral spinal cord in mice

Abstract: Optoelectronic systems can exert precise control over targeted neurons and pathways throughout the brain in untethered animals, but similar technologies for the spinal cord are not well established. Here, we describe a novel system for ultrafast, wireless, closed-loop manipulation of targeted neurons and pathways across the entire dorsoventral spinal cord in untethered mice. We developed a soft stretchable carrier integrating micro-LEDs that conforms to the dura matter of the spinal cord. A coating of silicone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…Optical fibers can also be integrated with advanced spinal endoscopes (white light and fluorescence) to complete molecular image-guided BSCB opening (29, 30). Furthermore, Opto-BSCB also has the potential to be used for studying neuromodulation in combination with chemogenetics (31) or optogenetics (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical fibers can also be integrated with advanced spinal endoscopes (white light and fluorescence) to complete molecular image-guided BSCB opening (29, 30). Furthermore, Opto-BSCB also has the potential to be used for studying neuromodulation in combination with chemogenetics (31) or optogenetics (16).…”
Section: Discussionmentioning
confidence: 99%
“…Light can be delivered to specific locations in the spinal cord with high spatiotemporal resolution. Recent studies have demonstrated implanted optoelectronic systems in the epidural space for optogenetic neuromodulation in the spinal cord (16). However, the use of genetic transfection could impede its further clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of large head-mounted device or implantation can induce tissue damage and irritation, which greatly hampers the in vivo application of optogenetics in freely moving animals. The emerging concept of "wireless Optogenetics" (20,(362)(363)(364)(365)(366)(367) aims at solving these hurdles and could be defined as a non-invasive or minimally invasive, precisely and remotely light-controlling platform for the studies of tissue biology, behavior and diseases in freely moving animals or primates. The advances in photonics, material engineering and nanofabrication technologies used in the semiconductor industry has been adapted for the application of wireless optogenetics (Table 3).…”
Section: Physiological Modulation In Vivo By Wireless Optogeneticsmentioning
confidence: 99%
“…Optogenetic modulation of spinal circuits in behaving animal models requires specialized optoelectronic devices. Indeed, the extensive displacements of spinal tissues relative to the vertebral column during unconstrained behaviors prevent the use of penetrating optical fibers or other classic approaches to deliver light throughout the spinal cord (Montgomery et al, 2015 ; Park et al, 2015 ; Lu et al, 2017 ; Kathe et al, 2021 ). Various devices have overcome the challenges of spinal cord optogenetics.…”
Section: Optogenetic Interrogation Of the Spinal Cord After Neurotraumamentioning
confidence: 99%
“…This deeply-penetrating photostimulation is achieved using the activation of red-shifted opsins since this wavelength of light is less attenuated by spinal tissue. Photostimulation is delivered through micro-LEDs that are integrated within a soft, stretchable carrier implanted over the dura mater (Kathe et al, 2021 ). This implant enabled us to study the role of proprioceptive feedback circuits in the production of walking enabled by serotonergic pharmacotherapy after complete SCI.…”
Section: Optogenetic Interrogation Of the Spinal Cord After Neurotraumamentioning
confidence: 99%